Eye Problems on Expeditions – Recommendation of the Medical Commission of the Union Internationale des Associations d’Alpinisme (UIAA) - D.S. Morris; J. Potts; S. Mella; D. Depla (Health Promotion & Physical Activity, 2020)
Visual loss in the wilderness setting is potentially fatal. Firstly it may be a warning sign of a serious systemic problem and secondly the patient may lose their functional independence and ability to respond to objective danger. The issues discussed in this paper fall broadly into two categories, those that are unique to the high altitude setting and those that could happen anywhere but require treatment to protect vision then standard ophthalmological care is unavailable. The aims are to provide practical knowledge on how to manage simple eye problems and also how to recognize the warning signs when evacuation may be required. In keeping with all wilderness medicine, preparation and prevention are essential to avoid eye problems in the mountains. This paper is intended for physicians, interested non-medical people and expedition operators as a practical guide to the treatment and prevention of eye problems on expeditions.